The role of twinning in sustainable care for children with cancer: A TIPPing point? SIOP PODC Working Group on Twinning, Collaboration, and Support. Issue 11 (22nd August 2020) - Kanwar, Vikramjit S.; Schwartz, Kevin R.; Salifu, Nihad; Abdelfattah, Ahmed M.; Anim, Bernard; Cayrol, Julie; Sniderman, Elizabeth; Eden, Tim
Abstract: With the World Health Organization (WHO) Global Initiative for Childhood Cancer, there is renewed interest in sustainable interventions to improve childhood cancer care in low‐/middle‐income countries (LMICs). Practitioners in LMICs have traditionally practiced "twinning, " i.e., targeted international pediatric oncology partnerships (TIPPs) between one or more institutions in a high‐income country (HIC) and an LMIC, to improve care for children with cancer in the latter. The International Society of Paediatric Oncology Committee for Paediatric Oncology in Developing Countries Working Group on Twinning, Collaboration, and Support reviewed guidelines from https://cancerpointe.com and the current literature, gathered input from practitioners in LMICs, and in this article discuss the role of TIPPs in the WHO initiative.